Histone content increases in differentiating embryonic stem cells - Karnavas, Theodoros; Pintonello, Luisa; Agresti, Alessandra; Bianchi, Marco E. (Frontiers in Physiology, 2014)
Mouse embryonic stem cells (ESCs) are pluripotent mammalian cells derived from the inner cell mass (ICM) of mouse blastocysts, which give rise to all three embryonic germ layers both in vivo and in vitro. Mouse ESCs share a distinct epigenetic landscape and a more decondensed chromatin compared to differentiated cells. Numerous studies have shown that distinct histone modifications in ESCs serve as landmarks of pluripotency. However, so far it is still unknown whether the total histone amount (as opposed to histone modifications) in cells of different developmental stage and differentiation capacity remains the same. In this work we show that the total histone content differs between pluripotent and differentiated cells. In vitro spontaneous differentiation from ESCs to Embryoid Bodies (EBs) and directed differentiation towards neuronal and endodermal cells entails an increase in histone content. Primary MEFs also contain more histones than ESCs. We suggest that the difference in histone content is an additional landmark of pluripotency, in addition to and besides histone modifications.